Literary images of Russia in Vladimir Sorokin’s novels - Kozárová, Zuzana (Studia Rossica Posnaniensia, 2024)
Vladimir Sorokin is one of the representatives of Russian postmodernism and one of the most translated contemporary Russian authors in Europe. His work reflects an alternative to the “accepted” Russian reality, focusing on its understanding and the influence it has on the Russian people. The author uses artistic means of expression without embellishment and through his works he reflects not only the political, economic and social situation, but also his views and attitudes as a resident of Russia. In our article we present the time map of Russia according to Sorokin as reflected in three novels: The queue (1985), representing the Soviet system in the country, Their four hearts (1994), depicting the collapse of the USSR, and Day of the oprichnik (2006), portraying the beginning of the XXI century. The article is devoted to the significant epochs of Russian history through the eyes of the author, who is trying to capture the mentality, beliefs and opinions of Russian people in his literary works. The analysis of the main periods of Russian history and their influence on the people, as reflected in Sorokin’s oeuvre, allows us to understand their attitude to the current situation in Russia.